Finite element buckling analysis of double-layered graphene nanoribbons. (8th February 2019) - Namnabat, Mohammad Sadegh; Barzegar, Amin; Javanbakht, Mahdi
Abstract: In this paper, the molecular structural mechanics method is applied to assess the critical buckling stress of double-layered graphene nanoribbons (DLGNRs) for different types of chirality, stacking modes and aspect ratios. In the developed atomistic model, the DLGNRs are considered as space-frame structures, in which the interlayer van der Waals (vdW) interactions and the in-plane covalent bonds are modeled as truss and beam elements, respectively. The beam sectional properties are obtained by establishing a conjunction between the structural and molecular mechanics. The Lennard-Jones potential is used to derive the elastic properties of the truss rod elements. The finite element method is employed for an eigenvalue-based buckling analysis. The results show that the critical buckling stress of the DLGNRs increases with increasing the mode shape number and decreases with increasing the aspect ratio for both the inphase and the antiphase modes for different types of chirality and stacking modes. Also, it is found that for the inphase modes, the critical buckling stress reaches its maximum value for the configuration with AA stacking mode and armchair chirality for all the aspect ratios. In the antiphase modes, the configuration with the highest stability is dependent on the aspect ratio. For the aspect ratios below 10, the configuration with AB stacking mode and armchair chirality has the highest stability; however, on the other hand, by increasing the aspect ratio above 10, the configuration with AB stacking mode and zigzag chirality represents the highest stability.